Answer:
A. The solution is (1, -3)
Explanation:
4x - 5y = 19
y = x - 4
Since the second equation already has y isolated, you can just plug that into the first equation:
4x - 5(x - 4) = 19
4x - 5x + 20 = 19
-x = -1
x = 1
Take your x value from the previous equation answer and plug that into the second equation:
y = (1) - 4
y = -3
Final solution:
(1, -3)
If you really want to know if you're correct, just do a LS/RS check for both equations:
4(1) - 5(-3) = 19
19 = 19
LS = RS
-3 = 1 - 4
-3 = -3
LS = RS